Studi Terapan Gaya Desain Interior Jepang Restoran Tomoto, Imari, Kayu, Nishiki Surabaya - Eveline Widjaja (Intra, 2013)
Applied studies in interior design style Japanese restaurant tomoto, Imari, Wood, Nishiki, Surabaya has been the subject of research that analyzed from the viewpoint of Japanese design style. Restaurant is a place of business or building that provides food and beverages which managed commercially by providing good service to all visitors. The application of different Japanese design style at every restaurant draw researchers to examine more in terms of the concept of Japanese design style. The implementation of the concept in the form of Japanese design style layout, interior elements, furniture to decorative elements are displayed on every restaurant under study.